Long-Range Planning—Challenge to Management Science - Drucker, Peter F. (Management Science, 1959)
This paper attempts to define long-range planning as the organized process of making entrepreneurial decisions. It tries to answer three questions asked by managers and management scientists when they hear the phrase “long-range planning”: What long-range planning is and what it is not; why it is needed; and what is needed to do long-range planning. The paper concludes with a brief statement why long-range planning can be considered a major opportunity for, and challenge to, Management Science.